2018
DOI: 10.1002/ejoc.201701769
|View full text |Cite
|
Sign up to set email alerts
|

Potent Analogues of Abscisic Acid – Identifying Cyano‐Cyclopropyl Moieties as Promising Replacements for the Cyclohexenone Headgroup

Abstract: Synthetic analogues of plant hormone abscisic acid (ABA) bearing a yet unexplored head group motif were prepared based on a combination of agrochemical experience, in vivo hits and structure‐based design. It could thus be explored how modifying key parts of ABA's cyclohexenone unit influenced receptor affinity and in vivo efficacy against drought stress in selected crops. Cyano‐cyclopropyl groups proved to be suitable replacements of the cyclohexanone moiety leading to ABA analogues with strong activity in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…The improvement of iWUE in C 3 crops such as wheat could be achieved either by genetic means or by using ABA agonists selective for distinct ABA receptors. Some ABA agonists have been identified with preferential binding to distinct ABA receptors (Benson et al, 2015;Helander et al, 2016;Vaidya et al, 2017;Frackenpohl et al, 2018aFrackenpohl et al, , 2018b. Engineering of ABA receptors for novel ligands offers another approach to activate a unique ABA receptor (Park et al, 2015) or the modulated expression of ABA receptor components as shown for Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of iWUE in C 3 crops such as wheat could be achieved either by genetic means or by using ABA agonists selective for distinct ABA receptors. Some ABA agonists have been identified with preferential binding to distinct ABA receptors (Benson et al, 2015;Helander et al, 2016;Vaidya et al, 2017;Frackenpohl et al, 2018aFrackenpohl et al, , 2018b. Engineering of ABA receptors for novel ligands offers another approach to activate a unique ABA receptor (Park et al, 2015) or the modulated expression of ABA receptor components as shown for Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, application of ABA and ABA agonists (Okamoto et al, 2013;Park et al, 2015;Cao et al, 2017), ectopic expression of ABA receptors (Santiago et al, 2009;Mosquna et al, 2011;Pizzio et al, 2013;González-Guzmán et al, 2014;Yang et al, 2016;Zhao et al, 2016), and reduced expression of ABA coreceptors (Rubio et al, 2009;Antoni et al, 2012) have been shown to minimize plant transpiration, and in several cases to boost survival rates under severe water deficit. A plethora of ABA agonists (Wilen et al, 1993;Benson et al, 2015;Vaidya et al, 2017;Frackenpohl et al, 2018aFrackenpohl et al, , 2018bNemoto et al, 2018) and antagonists (Takeuchi et al, 2014;Ito et al, 2015;Rajagopalan et al, 2016;Ye et al, 2017) were developed that allow the modulation of ABA responses.…”
mentioning
confidence: 99%
“…Further experimental details have been described in the suppl. material, as well as in references, [31,32] and. [42] Ethyl 3-{2-[1,1'-bi(cyclopropyl)-2-ylamino]-5-nitrophenyl}propanoate (650 mg, 2.04 mmol) was dissolved in abs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that cyano-cyclopropyl groups in ABA analogues 2 a-c served as isosteres of the cyclohexanone moiety giving rise to compounds with strong activity in vitro and in vivo. [22] Synthetic agonists of RCAR/(PYR/PYL) receptor proteins have also been prepared by other groups, [23][24][25] and the independent studies have afforded three different generations of sulfonamide lead structures. Likewise, naphthyl sulfonamides, such as 1 st generation lead structure pyrabactin 3 a, [26,27] structurally related pyrimidine 3 b, as well as five-membered analogs 4 a-b, [28] have all exhibited good initial receptor affinity, albeit paired with moderate beneficial effects in in vivo tests (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…5 However, because ABA itself induces negative effects on growth and is degraded quickly, ABA derivatives have been studied intensively. [6][7][8] Alternatively, a chemical that activates specific parts of the ABA signaling could be used for improving crop stress tolerance and for studying physiological mechanisms of stress responses.…”
Section: Introductionmentioning
confidence: 99%